COL4A3 mutation is an independent risk factor for poor prognosis in children with Alport syndrome - ALPAY, HARİKA (SPRINGER, 2020)
Background Alport syndrome (AS) is an inherited glomerular disease caused by mutations in COL4A3, COL4A4, or COL4A5. Associations between clinical manifestations and genotype are not yet well defined. Our study aimed to define clinical and genetic characteristics, establish genotype-phenotype correlations, and determine prognosis of AS in children. Methods A total of 87 children with AS from 10 pediatric nephrology centers, whom had genetic analyses performed at the Hacettepe University Nephrogenetics Laboratory between February 2017 and February 2019, were included. Data regarding demographics, family history, clinical and laboratory characteristics, histopathological and genetic test results, treatments, and yearly follow-up results were retrospectively analyzed. Results Of 87 patients, 16% presented with nephrotic syndrome. In patients with nephrotic syndrome, kidney biopsy findings showed focal segmental glomerulosclerosis (FSGS) in 79%, and COL4A3 mutations were the leading genetic abnormality (50%). Twenty-four percent of all patients progressed to chronic kidney disease (CKD). The rate of progression to CKD and the decline in the glomerular filtration rate of the patients with COL4A3 mutation were higher than other mutation groups (p < 0.001 and p = 0.04, respectively). In kidney survival analysis, nephrotic syndrome presentation, histopathology of FSGS, COL4A3 mutations, and autosomal recessive inheritance were found as independent risk factors for earlier progression to CKD. Cyclosporin A treatment did not improve kidney survival. Conclusions We emphasize that genetic testing is important for patients suspected as having AS. Furthermore, COL4A mutations should be considered in patients with FSGS and steroid-resistant nephrotic syndrome. This approach will shed light on the prognosis of patients and help with definitive diagnosis, preventing unnecessary and potentially harmful medications.
Keywords: Alport syndrome; COL4A mutations; Focal segmental glomerulosclerosis; Nephrotic syndrome; Cyclosporin A; GENOTYPE-PHENOTYPE CORRELATIONS; NATURAL-HISTORY; 195 FAMILIES; PROTEINURIA; MANAGEMENT; LOSARTAN; DISEASE; GENES